Rad23 stabilizes Rad4 from degradation by the Ub/proteasome pathway - Ortolan, Tatiana G. (Oxford University Press, 2004)
Rad23 protein interacts with the nucleotide excision-repair (NER) factor Rad4, and the dimer can bind damaged DNA. Rad23 also binds ubiquitinated proteins and promotes their degradation by the proteasome. Rad23/proteasome interaction is required for efficient NER, although the specific role of the Ub/proteasome system in DNA repair is unclear. We report that the availability of Rad4 contributes significantly to the cellular tolerance to UV light. Mutations in the proteasome, and in genes encoding the ubiquitin-conjugating enzymes Ubc4 and Ubc5, stabilized Rad4 and increased tolerance to UV light. A short amino acid sequence, previously identified in human Rad23, mediates the interaction between Rad23 and Rad4. We determined that this motif was required for stabilizing Rad4, and could function independently of the intact protein. A ubiquitin-like (UbL) domain in Rad23 binds the proteasome, and is required for conferring full resistance to DNA damage. However, Rad23/proteasome interaction appears unrelated to Rad23-mediated stabilization of Rad4. Specifically, simultaneous expression of a Rad23 mutant that could not bind the proteasome, with a mutant that could not interact with Rad4, fully suppressed the UV sensitivity of rad23Δ, demonstrating that Rad23 performs two independent, but concurrent roles in NER.